Invasive hepatocarcinoma of the bile ducts Icteric form. Three cases - Praderi, Raúl C; Navarrete, Héctor; Tiscornia, Eduardo; Fernández, Ricardo; Rodríguez, Gustavo (Cirugía del Uruguay, 1999)
The authors present three cases of hepatocarcinomas with obstructive intraductal sprouts. This type can a/so be associated to portal trombi as in one of the cases presented in this paper